Diagnostic challenges of lymphoma diagnosis: an unusual case of mantle cell lymphoma - Abdul Halim, Sarah; M Fuad, Fathy Nabila Najla (Faculty of Medicine, UKM, 2023)
Introduction: Mantle cell lymphoma (MCL) is a subtype of non-Hodgkin lymphoma. It is a mature B-cell neoplasm derived from the mantle zone of lymphoid follicles and is associated with CCND family rearrangements. Due to its nature, a correct diagnosis of MCL is needed to ensure timely treatment. Case report: A 68-yearold woman, with a history of follicular lymphoma from the tonsils, presented to our hospital with a one month history of progressive lethargy. On examination, a large right axillary mass was detected along with hepatomegaly. The blood film showed bicytopenia with leucoerythroblastic film and 17% abnormal lymphoid cells. The marrow aspirate was aparticulate with many abnormal lymphoid cells seen. Immunophenotyping revealed 23% abnormal lymphoid cells gated at bright CD45/low SSC. The lymphoid cells expressed bright CD20, CD5, positive CD19, dim CD200, CD79b, FMC7, CD38, heterogenous CD10 with lambda light chain restriction and negative for TdT and CD34. The trephine biopsy showed clusters of abnormal lymphoid cells. The cells have oval nuclei with small nucleoli. They are immunoreactive for CD20, CD5, Cyclin D, BCL2 with a proliferation index of 30-40%. A diagnosis of mantle cell lymphoma was made based on the IHC and immunophenotyping findings. FISH panel for IGH/CCND1 rearrangement and BCL2 rearrangement were performed however, both were negative. Discussion: The difficulty in the diagnosis was whether this is a CD5-positive-FL or MCL. CD-5-positive FL is associated with CD200 and CD43 expression with negative CD10 and a higher propensity for diffuse large B cell lymphoma (DLBCL) transformation. FL typically transforms into DLBCL, and transformation to mantle cell lymphoma has not been reported. This case demonstrated the need for extensive IHC panels and FISH studies complicated lymphoma cases for accurate diagnosis.